2005
DOI: 10.4049/jimmunol.174.2.854
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Dendritic Cell Phenotype and Interactions with CD4+ T Cells in Airway Inflammation and Tolerance

Abstract: An emerging concept is that different types of dendritic cells (DCs) initiate different immune outcomes, such as tolerance vs inflammation. In this study, we have characterized the DCs from the lung draining lymph nodes of mice immunized for allergic airway inflammation or tolerance and examined their interactions with CD4+ T cells. The DC population derived from tolerized mice was predominantly CD11c+, B220+, Gr-1+, CD11b−, and MHC class IIlow, which resembled plasmacytoid-type DCs whereas DCs from the inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
93
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(98 citation statements)
references
References 65 publications
4
93
0
1
Order By: Relevance
“…Overall, the morphology of the simvastatin-treated DCs was similar to the description of murine and human pDCs as we and others have described (ref. 20; Fig. 1B).…”
Section: Resultsmentioning
confidence: 99%
“…Overall, the morphology of the simvastatin-treated DCs was similar to the description of murine and human pDCs as we and others have described (ref. 20; Fig. 1B).…”
Section: Resultsmentioning
confidence: 99%
“…The precise subset of DC performing this tolerogenic role remains a matter of debate. Some investigators could show that tolerance induction and formation of Treg depends on an intact pDC system [9,36,37]. Others found that tolerance also required cDC that migrated to the MLN in a CCR7-dependent manner [38,39].…”
Section: Antigen Presentation and T-cell Polarizationmentioning
confidence: 99%
“…We and others have shown that pDC have an important role in inhalation tolerance and homeostasis in the lung. After administering OVA protein, pDC of the MLN take up OVA, but in contrast to lung-derived cDC, pDC are very poor at presenting OVA to CD4 1 T cells [9,37]. However, when pDC were specifically depleted using antibodies, inhalation tolerance to OVA no longer occurred and mice developed features of severe asthma, even in the total absence of any adjuvant.…”
Section: The Role Of Lung DC Subsets In Allergy and Asthmamentioning
confidence: 99%
“…The lung is known to benefit from the functions of two major subsets of DC, termed conventional myeloid DC (mDC), that express moderate to high levels of both CD11c+ and CD11b+, and a second subpopulation, termed plasmacytoid DC (pDC), that display cell-surface expression of PDCA-1 and low levels of CD11c [23][24][25][26][27] . Studies exploring the role of DC activation and allergic risk in asthma development have focused on the adjuvant potential of PM to induce allergic sensitization to a coadministered antigen-like ovalbumin (OVA) or house dust mite [6,12,18,[28][29][30][31][32] .…”
mentioning
confidence: 99%